PUBLIC TRANSPORT PLANNING: LOCAL BUS SERVICE INTEGRATION AND IMPROVEMENTS IN PENANG, MALAYSIA - Aziz, Azfizan; Mohamad, Jamilah (PLANNING MALAYSIA, 2020)
An integrated public transport system should provide seamless travel to passengers so that they can enjoy good service connection, reasonable waiting time at interchanges, comprehensive information and an integrated ticket amongst different transport modes. Such a system is essential because it allows integrated travel by using all public transport modes that suit passengers’ routes. The concept of integration in public transport, which includes physical, network, fare, information and institutional integration, generally adopts the vision of ‘good practice’ in terms of integration of public transport services. This research concentrates on bus service because it is the primary public transport mode in Penang, Malaysia. This work analyses the Rapid Penang Bus Operation and Network in detail by using a system of indicators derived from surveys and detailed information supplied by the operator. Several recommendations are also provided to improve the reliability, convenience, accessibility, coordinated physical effort and fair fare of bus services.